Positive electrode active material powder, positive electrode containing the same, and lithium secondary battery

JP2025505993AActive Publication Date: 2025-03-05LG ENERGY SOLUTION LTD
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
JP2024545999
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-02-11
Filing Date
2023-02-10
Publication Date
2025-03-05
Estimated Expiration
2043-02-10

AI Technical Summary

Benefits of technology

【0019】 単粒子または擬似単粒子の形態の過リチウム化マンガン系酸化物は、二次粒子の形態を有する従来の過リチウム化マンガン系酸化物と比べて、電解液との反応面積が少なく、且つ粒子強度が高くて、電極の製造時に圧延による粒子割れが小さいため、電解液との副反応によるガスの発生を最小化することができる。よって、本発明のように、単粒子または擬似単粒子の形態の過リチウム化マンガン系酸化物を正極活物質として用いる場合、ガスの発生量が著しく減少し、これにより、リチウム二次電池の寿命特性および安全性が向上する効果が得られる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025505993000001_ABST
    Figure 2025505993000001_ABST
Patent Text Reader

Abstract

The present invention relates to a positive electrode active material powder containing perlithiated manganese oxide particles, which are represented by the following chemical formula 1 and are in the form of a single particle consisting of one nodule or a pseudo-single particle that is a composite of 2 to 30 nodules, a positive electrode containing the positive electrode active material powder, and a lithium secondary battery. a Ni b Co c Mn d M e O2 (in the above chemical formula 1, 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] This application claims the benefit of priority based on Korean Patent Application No. 10-2022-0018478 filed on February 11, 2022, and all contents disclosed in the documents of the Korean patent application are incorporated as part of this specification.

[0002] The present invention relates to a positive electrode active material powder, a positive electrode containing the same, and a lithium secondary battery, and more particularly to a positive electrode active material powder containing a perlithiated manganese-based oxide in the form of a single particle or pseudo-single particle, and a positive electrode and a lithium secondary battery containing the same. [Background technology]

[0003] In recent years, interest in energy storage technology has been growing, and its application fields have expanded to include mobile phones, camcorders, and laptop computers, as well as the energy of electric vehicles. Accordingly, efforts in the research and development of electrochemical devices are being made concrete.

[0004] Among electrochemical devices, there has been growing interest in the development of rechargeable secondary batteries. In particular, lithium secondary batteries, developed in the early 1990s, have been attracting attention due to their advantages of high operating voltage and extremely high energy density.

[0005] Lithium secondary batteries are generally manufactured by forming an electrode assembly by interposing a separator between a positive electrode including a positive electrode active material made of a lithium-containing transition metal oxide and a negative electrode including a negative electrode active material capable of storing lithium ions, inserting the electrode assembly into a battery case, injecting a non-aqueous electrolyte that serves as a medium for transferring lithium ions, and then sealing the battery case. The non-aqueous electrolyte is generally composed of a lithium salt and an organic solvent capable of dissolving the lithium salt.

[0006] In the lithium secondary batteries developed to date, lithium nickel oxide is usually used as the positive electrode active material, and carbonaceous materials such as natural graphite and artificial graphite are used as the negative electrode active material. However, such conventional lithium secondary batteries cannot fully meet the energy density required for batteries for electric vehicles. Therefore, in order to achieve high capacity, methods of applying perlithiated manganese oxide containing excess lithium as the positive electrode active material and applying silicon-based negative electrode active material with high theoretical capacity as the negative electrode active material are being actively studied.

[0007] Perlithiated manganese oxides, which contain excess lithium, have a crystal structure that is a mixture of a layered structure phase (LiMO2) and a rock salt structure phase (Li2MnO3), and as the rock salt structure phase becomes activated during the charge and discharge process, additional capacity is generated through the oxygen redox reaction, allowing for high capacity to be achieved. However, there is a problem in that a large amount of gas is generated during the oxygen redox reaction, which changes the crystal structure of the positive electrode active material and reduces the life characteristics.

[0008] On the other hand, silicon-based negative electrode active materials can achieve a higher capacity than carbon-based negative electrode active materials, but they have a problem in that they have a large irreversible capacity and undergo large volume changes during charging and discharging, resulting in reduced life characteristics. Summary of the Invention [Problem to be solved by the invention]

[0009] The present invention has been made to solve the above problems, and aims to provide a positive electrode active material powder containing a perlithiated manganese oxide that generates little gas and can achieve excellent battery safety and life characteristics, and a positive electrode and a lithium secondary battery using the same. [Means for solving the problem]

[0010] According to one embodiment, the present invention provides a positive electrode active material powder containing manganese-based over-lithiated oxide particles represented by the following Chemical Formula 1, wherein the manganese-based over-lithiated oxide particles are in the form of single particles composed of one nodule or pseudo single particles which are composites of 2 to 30 nodules or less.

[0011] [Chemical Formula 1] Li a Ni b Co c Mn d M e O2

[0012] In Chemical Formula 1, M is at least one or more selected from the group consisting of Al, B, Co, W, Mg, V, Ti, Zn, Ga, In, Ru, Nb, Sn, Sr, and Zr, 1 < a, 0 ≤ b ≤ 0.5, 0 ≤ c ≤ 0.1, 0.5 ≤ d < 1.0, 0 ≤ e ≤ 0.2, preferably 1.1 ≤ a ≤ 1.5, 0.1 ≤ b ≤ 0.4, 0 ≤ c ≤ 0.05, 0.50 ≤ d ≤ 0.80, 0 ≤ e ≤ 0.1, and more preferably 1.1 ≤ a ≤ 1.3, 0.2 ≤ b ≤ 0.4, 0 ≤ c ≤ 0.05, 0.50 ≤ d ≤ 0.70, 0 ≤ e ≤ 0.1.

[0013] The positive electrode active material powder may be composed of positive electrode active material particles having at least one of the forms of the single particles and pseudo single particles.

[0014] The positive electrode active material powder has an average particle size D 50 which may be 7.0 μm or less, 0.5 μm to 7.0 μm, 0.5 μm to 6 μm, 1.0 μm to 6.0 μm, 2.0 μm to 6.0 μm, or 2.5 μm to 6.0 μm.

[0015] The manganese-based over-lithiated oxide may have an average particle size of nodules of 0.5 μm to 3.5 μm, 0.5 μm to 3 μm, 1 μm to 3 μm, or 1 μm to 2.5 μm.

[0016] The perlithiated manganese oxide may have a crystalline size of 30 nm to 400 nm, 30 nm to 300 nm, 50 nm to 300 nm, or 70 nm to 300 nm.

[0017] According to another embodiment, the present invention provides a positive electrode comprising the positive electrode active material powder according to the present invention.

[0018] According to another embodiment, the present invention provides a lithium secondary battery including a positive electrode containing the positive electrode active material powder according to the present invention, a negative electrode containing a negative electrode active material, a separator interposed between the positive electrode and the negative electrode, and an electrolyte. Effect of the Invention

[0019] Compared with conventional perlithiated manganese oxides having the form of secondary particles, perlithiated manganese oxides having the form of single particles or pseudo-single particles have a smaller reaction area with the electrolyte, have high particle strength, and are less likely to crack due to rolling during electrode manufacturing, so that gas generation due to side reactions with the electrolyte can be minimized. Therefore, when perlithiated manganese oxides having the form of single particles or pseudo-single particles are used as a positive electrode active material as in the present invention, the amount of gas generation is significantly reduced, thereby improving the life characteristics and safety of lithium secondary batteries.

[0020] In addition, the perlithiated manganese oxide contained in the positive electrode active material powder of the present invention has a crystal structure in which a rock salt Li2MnO3 phase and a layered LiM'O2 phase (where M' is Ni, Co, Mn) are mixed, and an excess amount of lithium is generated from the Li2MnO3 phase during the activation process, which can be used to compensate for the irreversible capacity of the negative electrode active material. Therefore, when the positive electrode active material of the present invention is used, the use of a sacrificial positive electrode material or prelithiation for compensating the negative electrode can be minimized, and the capacity of the positive electrode can be maximized. [Brief description of the drawings]

[0021] [Figure 1]2 is a SEM photograph of the positive electrode active material powder produced in Example 1. [Diagram 2] 2 is a SEM photograph of the positive electrode active material powder produced in Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0022] The terms and words used in this specification and the claims are not to be interpreted in a limited manner to their ordinary or dictionary meanings, but are to be interpreted in a meaning and concept that is consistent with the technical idea of ​​the present invention, based on the principle that an inventor can appropriately define the concept of a term in order to best describe his / her invention.

[0023] In the present invention, a "single particle" is a particle consisting of one single nodule. In the present invention, a "quasi-single particle" means a particle that is a complex formed from 30 or less nodules.

[0024] In the present invention, the term "nodule" refers to a sub-particle unit body constituting a single particle or a quasi-single particle, and the nodule may be a single crystal having no crystalline grain boundary, or may be a polycrystal having no apparent grain boundary when observed at a magnification of 5,000 to 20,000 using a scanning electron microscope (SEM).

[0025] In the present invention, the term "secondary particle" refers to a particle formed by agglomeration of several tens to several hundreds of primary particles. More specifically, a secondary particle is an agglomeration of 40 or more primary particles.

[0026] The term "particle" as used in the present invention may include any one or all of a single particle, a quasi-single particle, a primary particle, a nodule, and a secondary particle.

[0027] In the present invention, the "average particle size D 50" means the particle size at 50% of the volume cumulative particle size distribution of the positive electrode active material powder. 50 can be measured by a laser diffraction method. For example, the positive electrode active material powder is dispersed in a dispersion medium, introduced into a commercially available laser diffraction particle size measuring device (e.g., Microtrac MT 3000), and irradiated with ultrasonic waves of about 28 kHz at an output of 60 W, and a volume cumulative particle size distribution graph is obtained, and the particle size corresponding to 50% of the volume cumulative amount is obtained.

[0028] In the present invention, the average particle size of the primary particles or nodules can be measured by image analysis. Specifically, an image of the particles is obtained using a device such as a scanning electron microscope (SEM) or electron backscatter diffraction (EBSD), the particle sizes of the primary particles or nodules confirmed from the obtained image are measured, and then the arithmetic average value of these is calculated to measure the average particle size.

[0029] In the present invention, the "crystalline size" can be quantitatively analyzed by X-ray diffraction analysis (XRD) using CuKα X-rays. Specifically, the crystalline size can be quantitatively analyzed by placing the particles to be measured in a holder, irradiating the particles with X-rays, and analyzing the diffraction pattern. Sampling is performed by placing a powder sample of the particles to be measured in a recessed groove in the center of a general powder holder, making the surface uniform using a slide glass, and preparing the sample so that the height is equal to the edge of the holder. Then, X-ray diffraction analysis is performed using a Bruker D8 Endeavor (light source: CuKα, λ=1.54Å) equipped with a LynxEye XE-T position sensitive detector under the conditions of FDS 0.5°, 2θ=15°~90° region, step size 0.02°, and total scan time of about 20 minutes. The measured data is subjected to Rietveld refinement, taking into account the charge at each site (metal ions at transition metal sites are +3, Ni ions at Li sites are +2) and cation mixing. When analyzing the crystallite size, instrumental broadening is taken into account using the Fundamental Parameter Approach (FPA) implemented in the Bruker TOPAS program, and the entire peak in the measurement range is used during fitting. Peak shape is fitted using only the Lorenzian contribution as the First Principle (FP) of the peak types available in TOPAS, and strain is not considered in this case.

[0030] In order to solve the problems of gas generation and deterioration of life characteristics in secondary batteries using over-lithiated manganese-based oxides, the inventors repeated research. As a result, it was found that by forming the over-lithiated manganese-based oxides in the form of single particles composed of one nodule and / or pseudo-single particles which are composites of 30 nodules or less, the amount of gas generation can be reduced and the life characteristics can be significantly improved.

[0031] Specifically, the positive electrode active material powder according to the present invention contains over-lithiated manganese-based oxide particles represented by the following Chemical Formula 1, and the over-lithiated manganese-based oxide particles are in the form of single particles composed of one nodule or pseudo-single particles which are composites of 2 to 30 nodules or less.

[0032] [Chemical Formula 1] Li a Ni b Co c Mn d M e O2

[0033] In Chemical Formula 1, M is at least one selected from the group consisting of Al, B, Co, W, Mg, V, Ti, Zn, Ga, In, Ru, Nb, Sn, Sr, and Zr, 1 < a, 0 ≦ b ≦ 0.5, 0 ≦ c ≦ 0.1, 0.5 ≦ d < 1.0, 0 ≦ e ≦ 0.2, preferably 1.1 ≦ a ≦ 1.5, 0.1 ≦ b ≦ 0.4, 0 ≦ c ≦ 0.05, 0.50 ≦ d ≦ 0.80, 0 ≦ e ≦ 0.1, and more preferably 1.1 ≦ a ≦ 1.3, 0.2 ≦ b ≦ 0.4, 0 ≦ c ≦ 0.05, 0.50 ≦ d ≦ 0.70, 0 ≦ e ≦ 0.1.

[0034] Hereinafter, the present invention will be described in more detail.

[0035] Positive electrode active material powder The positive electrode active material powder according to the present invention includes perlithiated manganese oxide particles in the form of a single particle consisting of one nodule, or a pseudo-single particle that is a composite of 2 to 30 nodules. Preferably, the positive electrode active material powder may be composed of positive electrode active material particles having at least one of the form of the single particle and the pseudo-single particle.

[0036] Conventional perlithiated manganese oxide particles are generally in the form of spherical secondary particles formed by agglomeration of tens to hundreds of primary particles. However, secondary particles formed by agglomeration of many primary particles are prone to particle cracking, in which the primary particles separate during the rolling process in the manufacture of the positive electrode, and cracks occur inside the particles during charging and discharging. In addition, the contact area with the electrolyte increases, increasing gas generation and active material degradation due to side reactions with the electrolyte, which leads to a problem of reduced life characteristics.

[0037] In contrast, when perlithiated manganese oxide particles are formed in the form of single particles or pseudo-single particles as in the present invention, the particle strength is higher than that of conventional perlithiated manganese oxide particles in the form of secondary particles, so there is less particle cracking during rolling, and the number of sub-particle units constituting the particles is small, so there is less change due to volume expansion and contraction of the sub-particle units during charging and discharging, and the occurrence of cracks inside the particles is significantly reduced.In addition, single particles or pseudo-single particles have a smaller reaction area with the electrolyte than secondary particles, so gas generation due to side reactions with the electrolyte is also reduced.

[0038] The perlithiated manganese oxide particles according to the present invention may have a composition represented by the following chemical formula 1.

[0039] [Chemical formula 1] Li a Ni b Co c Mn d M e O2

[0040] In the above Chemical Formula 1, M may be at least one selected from the group consisting of Al, B, Co, W, Mg, V, Ti, Zn, Ga, In, Ru, Nb, Sn, Sr, and Zr.

[0041] On the other hand, a is the molar ratio of Li in the over-lithiated manganese-based oxide, and it may be 1 < a, 1.1 ≤ a ≤ 1.5, or 1.1 ≤ a ≤ 1.3. When a satisfies the above range, a crystal structure in which a layered structure phase and a rock salt structure phase are mixed can be formed, and the capacity due to the oxygen-redox reaction during charge and discharge can be realized, and high capacity characteristics can be realized.

[0042] The above b is the molar ratio of Ni in the over-lithiated manganese-based oxide, and it may be 0 ≤ b ≤ 0.5, 0.1 ≤ b ≤ 0.4, or 0.2 ≤ b ≤ 0.4.

[0043] The above c is the molar ratio of Co in the over-lithiated manganese-based oxide, and it may be 0 ≤ c ≤ 0.1, 0 ≤ c ≤ 0.08, or 0 ≤ c ≤ 0.05. When c exceeds 0.1, it is difficult to ensure high capacity, gas generation and degradation of the positive electrode active material become severe, and the life characteristics may deteriorate.

[0044] The above d is the molar ratio of Mn in the over-lithiated manganese-based oxide, and it may be 0.5 ≤ d < 1.0, 0.50 ≤ d ≤ 0.80, or 0.50 ≤ d ≤ 0.70. When d is less than 0.5, the proportion of the rock salt structure phase becomes excessively small and the effect of capacity improvement becomes negligible.

[0045] The above e is the molar ratio of the doping element M in the over-lithiated manganese-based oxide, and it may be 0 ≤ e ≤ 0.2, 0 ≤ e ≤ 0.1, or 0 ≤ e ≤ 0.05. If the content of the doping element is too much, it may have an adverse effect on the active material capacity.

[0046] The perlithiated manganese oxide has a crystal structure in which a layered structure phase (LiMO2) and a rock salt structure phase (Li2MnO3) are mixed. As the rock salt structure phase is activated at a high voltage of 4.4 V or more, additional capacity can be realized by the oxygen-redox reaction during charging and discharging, and thus high capacity can be realized.

[0047] Meanwhile, in the perlithiated manganese oxide represented by the chemical formula 1, the ratio of the number of moles of Li to the number of moles of all metal elements excluding Li (Li / Me) may be 1.2 to 1.5, 1.25 to 1.5, or 1.25 to 1.4. When the Li / Me ratio satisfies the above range, excellent rate characteristics and capacity characteristics are exhibited. If the Li / Me ratio is too high, the electrical conductivity may decrease and the rock salt structure phase (Li2MnO3) may increase, which may increase the rate of degeneration, and if it is too low, the effect of improving the energy density may be insignificant.

[0048] Meanwhile, the composition of the perlithiated manganese oxide may be represented by the following Chemical Formula 2.

[0049] [Chemical formula 2] XLi2MnO3·(1-X)Li[Ni 1-y-z-w Mn y Co z M w ]O2

[0050] In the above Chemical Formula 2, M may be at least one metal ion selected from the group consisting of Al, B, Co, W, Mg, V, Ti, Zn, Ga, In, Ru, Nb, Sn, Sr, and Zr.

[0051] The X means the proportion of the Li2MnO3 phase in the perlithiated manganese oxide, and may be 0.2≦X≦0.5, 0.25≦X≦0.5, or 0.25≦X≦0.4. When the proportion of the Li2MnO3 phase in the perlithiated manganese oxide satisfies the above range, high capacity characteristics can be achieved.

[0052] The y is LiM'O2 (where M' = Ni 1-y-z-w Mny Co z M w ) the molar ratio of Mn in the layered structure phase, and may be 0.4≦y<1, 0.4≦y≦0.8, or 0.4≦y≦0.7.

[0053] The z is a molar ratio of Co in the LiM'O2 layered structure phase, and may be 0≦z≦0.1, 0≦z≦0.08, or 0≦z≦0.05. If z exceeds 0.1, gas generation and degradation of the positive electrode active material become severe, and the life characteristics may be reduced.

[0054] The w is the molar ratio of the doping element M in the LiM'O2 layer, and may be 0≦w≦0.2, 0≦w≦0.1, or 0≦w≦0.05.

[0055] On the other hand, in the perlithiated manganese oxide, the average particle size of the nodules may be 0.5 μm or more, 1.0 μm or more, 1.5 μm or more, and 3.5 μm or less, 3 μm or less, 2.5 μm or less, or 2.0 μm or less. The average particle size of the nodules may be 0.5 μm to 3.5 μm. For example, the average particle size of the nodules may be 0.5 μm to 3.5 μm, 0.5 μm to 3 μm, 1 μm to 3 μm, or 1 μm to 2.5 μm. If the average particle size of the nodules is less than 0.5 μm, the overall specific surface area of ​​the positive electrode active material may increase, which may increase side reactions of the electrolyte, and if it exceeds 3.5 μm, the lithium mobility in the positive electrode active material may decrease, which may decrease the output characteristics of the battery.

[0056] The perlithiated manganese oxide may have a crystallite size of 30 nm to 400 nm, preferably 30 nm to 300 nm, more preferably 50 nm to 300 nm, and even more preferably 70 nm to 300 nm. When the crystallite size satisfies the above range, the degree of completion of the crystal structure can be improved and excellent electrochemical performance can be ensured. If the crystallite size is too small, the crystal structure is not sufficiently formed, so that the stability of the crystal structure is reduced, which may result in a reduced life performance and increased gas generation. On the other hand, if the crystallite size is too large, although the structural stability is increased, there is a risk of an impurity structure being generated on the surface, which may increase the resistance, and the Li migration path may be lengthened, which may result in a reduced rate characteristic.

[0057] Meanwhile, the perlithiated manganese-based oxide may be prepared by mixing a transition metal precursor and a lithium source material and then calcining the mixture.

[0058] Examples of the lithium source material include lithium-containing carbonates (e.g., lithium carbonate, etc.), hydrates (e.g., lithium hydroxide hydrate (LiOH·H2O)), hydroxides (e.g., lithium hydroxide), nitrates (e.g., lithium nitrate (LiNO3)), chlorides (e.g., lithium chloride (LiCl)), etc., and one of these can be used alone or a mixture of two or more can be used.

[0059] Meanwhile, the transition metal precursor may be in the form of a hydroxide, an oxide, or a carbonate. When a precursor in the form of a carbonate is used, it is more preferable since a positive electrode active material having a relatively high specific surface area can be produced.

[0060] The transition metal precursor may be prepared by a co-precipitation process. For example, the transition metal precursor may be prepared by dissolving each transition metal-containing raw material in a solvent to prepare a metal solution, and then mixing the metal solution, an ammonium cation complexing agent, and a basic compound, and then carrying out a co-precipitation reaction. If necessary, an oxidizing agent or oxygen gas may be further added during the co-precipitation reaction.

[0061] In this case, the transition metal-containing raw material may be acetate, carbonate, nitrate, sulfate, halide, sulfide, etc. of each transition metal. For example, the transition metal-containing raw material may be NiO, NiCO3·2Ni(OH)2·4H2O, NiC2O2·2H2O, Ni(NO3)2·6H2O, NiSO4, NiSO4·6H2O, Mn2O3, MnO2, Mn3O4MnCO3, Mn(NO3)2, MnSO4H2O, manganese acetate, manganese halide, cobalt oxide, cobalt sulfate, cobalt nitrate, cobalt carbonate, cobalt acetate, cobalt halide, etc.

[0062] The ammonium cation complexing agent may be at least one selected from the group consisting of NH4OH, (NH4)2SO4, NH4NO3, NH4Cl, CH3COONH4, and NH4CO3.

[0063] The basic compound may be at least one selected from the group consisting of NaOH, Na2CO3, KOH, and Ca(OH)2. The form of the precursor may vary depending on the type of basic compound used. For example, when NaOH is used as the basic compound, a precursor in the form of a hydroxide is obtained, and when Na2CO3 is used as the basic compound, a precursor in the form of a carbonate is obtained. When a basic compound and an oxidizing agent are both used, a precursor in the form of an oxide is obtained.

[0064] Meanwhile, the transition metal precursor and the lithium source material may be mixed in amounts such that the molar ratio of total transition metals (Ni+Co+Mn):Li is 1:1.05 to 1:2, preferably 1:1.1 to 1:1.8, and more preferably 1:1.3 to 1:1.8.

[0065] Meanwhile, the calcination is carried out at a temperature at which single particles or pseudo-single particles can be formed. In order to form single particles or pseudo-single particles, the calcination needs to be carried out at a higher temperature than that used in the manufacture of conventional lithium transition metal composite oxides in the form of secondary particles. For example, when the precursor composition is the same, the calcination needs to be carried out at a temperature about 30°C to 100°C higher than that used in the manufacture of conventional lithium transition metal composite oxides in the form of secondary particles. The calcination temperature for forming single particles or pseudo-single particles may vary depending on the metal composition in the precursor, and may be, for example, about 800°C to 1100°C, preferably about 950°C to 1050°C.

[0066] The firing may be carried out for 5 to 35 hours in an oxygen atmosphere. Here, the oxygen atmosphere means an atmosphere containing a sufficient amount of oxygen for firing, including an air atmosphere. In particular, it is preferable to carry out the firing in an atmosphere having an oxygen partial pressure higher than that of the air atmosphere.

[0067] Meanwhile, the positive electrode active material according to the present invention may further include a coating layer on the surface of the perlithiated manganese oxide particles, if necessary. When the positive electrode active material includes a coating layer, the coating layer suppresses contact between the perlithiated manganese oxide and the electrolyte, reducing electrolyte side reactions, thereby achieving better gas reduction and improved life characteristics.

[0068] The coating layer is a coating element M 1 and the coating element M 1is, for example, at least one selected from the group consisting of Al, B, Co, W, Mg, V, Ti, Zn, Ga, In, Ru, Nb, Sn, Sr, and Zr, and may be preferably Al, Co, Nb, W, and combinations thereof, and more preferably Al, Co, and combinations thereof. 1 may contain two or more elements, for example, Al and Co. The coating elements are in the form of oxides in the coating layer, i.e., M 1 It can exist in Oz (1≦z≦4).

[0069] The coating layer can be formed by dry coating, wet coating, chemical vapor deposition (CVD), physical vapor deposition (PVD), atomic layer deposition (ALD), etc. Among them, the coating layer is preferably formed by atomic layer deposition, since the coating layer can be formed over a wide area.

[0070] The area where the coating layer is formed may be 10 to 100%, preferably 30 to 100%, and more preferably 50 to 100%, based on the total surface area of ​​the perlithiated manganese oxide particles.

[0071] On the other hand, the positive electrode active material powder according to the present invention has an average particle size D 50 However, it may be 7.0 μm or less, 0.5 μm to 7.0 μm, 0.5 μm to 6 μm, 1.0 μm to 6.0 μm, 2.0 μm to 6.0 μm, or 2.5 μm to 6.0 μm. 50 If the thickness exceeds 7.0 μm, the resistance increases and the output characteristics decrease.

[0072] The positive electrode active material powder has a BET specific surface area of ​​0.1 to 6 m 2 / g or 0.1~5m 2 / g. When the BET specific surface area of ​​the positive electrode active material powder satisfies the above range, appropriate electrochemical properties can be ensured. If the specific surface area is too small, the electrochemical properties may be deteriorated due to a decrease in reaction sites, and if it is too large, the reaction area with the electrolyte may increase, which may further activate side reactions at high voltages.

[0073] In addition, the positive electrode active material powder according to the present invention preferably has an initial irreversible capacity of about 5 to 70%, 5 to 50%, or 10 to 30%. When the initial irreversible capacity of the positive electrode active material satisfies the above range, the irreversible capacity of the silicon-based negative electrode active material can be compensated for without the use of another compensation material such as a sacrificial positive electrode material or a process for recompensing lithium such as prelithiation.

[0074] positive electrode Next, the positive electrode according to the present invention will be described.

[0075] The positive electrode according to the present invention includes a positive electrode active material powder containing a perlithiated manganese oxide in the form of a single particle or pseudo-single particle according to the present invention. Specifically, the positive electrode includes a positive electrode current collector and a positive electrode active material layer formed on the positive electrode current collector and containing the positive electrode active material powder. The positive electrode active material powder has been described above, so other components will be described below.

[0076] In the positive electrode, the positive electrode current collector is not particularly limited as long as it does not induce chemical changes in the battery and has conductivity, and for example, stainless steel, aluminum, nickel, titanium, baked carbon, or aluminum or stainless steel surface treated with carbon, nickel, titanium, silver, etc. may be used. The positive electrode current collector usually has a thickness of 3 μm to 500 μm, and fine irregularities may be formed on the surface of the positive electrode current collector to increase the adhesive force of the positive electrode active material. For example, it may be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.

[0077] On the other hand, the positive electrode active material layer may contain a conductive material and a binder in addition to the positive electrode active material powder.

[0078] The conductive material is used to impart conductivity to the electrode, and can be used without any particular limitation as long as it does not cause a chemical change in the battery that is constructed and has electronic conductivity. Specific examples include graphite such as natural graphite and artificial graphite; carbon-based materials such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, carbon fiber, and carbon nanotubes; metal powder or metal fiber such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive polymers such as polyphenylene derivatives, and one of these can be used alone or a mixture of two or more of them can be used. The conductive material may be usually contained in an amount of 1 to 30% by weight, preferably 1 to 20% by weight, and more preferably 1 to 10% by weight, based on the total weight of the positive electrode active material layer.

[0079] The binder plays a role of improving the adhesion between the positive electrode active material particles and the adhesive strength between the positive electrode active material and the positive electrode current collector. Specific examples include polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer rubber (EPDM rubber), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, or various copolymers thereof, and one of these can be used alone or a mixture of two or more can be used. The binder may be contained in an amount of 1 to 30% by weight, preferably 1 to 20% by weight, more preferably 1 to 10% by weight, based on the total weight of the positive electrode active material layer.

[0080] The positive electrode may be manufactured by a conventional method for manufacturing a positive electrode. For example, the positive electrode may be manufactured by mixing a positive electrode active material, a binder, and / or a conductive material in a solvent to prepare a positive electrode slurry, applying the positive electrode slurry onto a positive electrode current collector, and then drying and rolling the positive electrode slurry. In this case, the types and contents of the positive electrode active material, binder, and conductive material are as described above.

[0081] The solvent may be any solvent commonly used in the art, such as dimethyl sulfoxide (DMSO), isopropyl alcohol, N-methylpyrrolidone (NMP), acetone, or water, and one or more of these may be used alone or in combination. The amount of the solvent used may be sufficient to dissolve or disperse the positive electrode active material, conductive material, and binder, and to provide a viscosity that allows excellent thickness uniformity during subsequent coating for the production of a positive electrode, taking into consideration the coating thickness of the slurry and the production yield.

[0082] Alternatively, the positive electrode can be produced by casting the positive electrode slurry on a separate support, peeling the resulting film from the support, and laminating the film on a positive electrode current collector.

[0083] Lithium secondary battery The lithium secondary battery of the present invention comprises a positive electrode containing the positive electrode active material powder according to the present invention, a negative electrode containing a negative electrode active material, a separator interposed between the positive electrode and the negative electrode, and an electrolyte.

[0084] When using the positive electrode active material powder according to the present invention, after performing an activation process at a high voltage of 4.6 V or more, it is possible to achieve a high energy density by repeatedly charging and discharging at a charge cut-off voltage of 4.2 to 4.5 V, and it is possible to minimize the deterioration of life characteristics due to gas generation.

[0085] In addition, since the perlithiated manganese oxide represented by Chemical Formula 1 has a high initial irreversible capacity, even when it is used together with a negative electrode active material having a large irreversible capacity such as a silicon-based negative electrode active material, it is possible to minimize the addition of a sacrificial positive electrode material or prelithiation to compensate for the irreversible capacity of the negative electrode active material.

[0086] The positive electrode has been described above, so the other components will be described below.

[0087] negative electrode The negative electrode according to the present invention includes a negative electrode active material layer containing a negative electrode active material, and the negative electrode active material layer may further include a conductive material and / or a binder, as necessary.

[0088] As the negative electrode active material, various negative electrode active materials used in the art, such as silicon-based negative electrode active materials, carbon-based negative electrode active materials, metal alloys, etc. may be used.

[0089] Preferably, the negative electrode active material includes a silicon-based negative electrode active material.

[0090] Silicon-based negative electrode active materials have a higher theoretical capacity and a faster reaction rate with lithium than carbon-based negative electrode active materials, and therefore, when a silicon-based negative electrode active material is included in a negative electrode, the energy density and rapid charging performance are improved. However, silicon-based negative electrode active materials have a large irreversible capacity and a large volume expansion during charging and discharging, which leads to deterioration in terms of life characteristics. In particular, when used in combination with a perlithiated manganese oxide that generates a lot of gas, there is a problem that the deterioration of life characteristics is more severe. However, when a perlithiated manganese oxide in the form of a single particle or pseudo-single particle is applied as in the present invention, the deterioration of life characteristics can be minimized because less gas is generated than in the conventional perlithiated manganese oxide in the form of secondary particles, and the excess lithium generated from the phase of Chemical Formula 2 during the activation of the perlithiated manganese oxide can compensate for the irreversible capacity of the silicon-based negative electrode active material.

[0091] The silicon-based negative electrode active material is, for example, Si, SiOw (Here, 0 < w ≤ 2), Si-C composite, Si-M a alloy (M a is one or more selected from the group consisting of Al, Sn, Mg, Cu, Fe, Pb, Zn, Mn, Cr, Ti, Ni), or a combination thereof may also be acceptable.

[0092] On the other hand, the silicon-based negative electrode active material may, if necessary, be doped with M b metal, and in this case, the M b metal may be an alkali metal element of Group 1 and / or an alkaline earth metal element of Group 2, and for example, Li, Mg, etc. may also be acceptable. Specifically, the silicon negative electrode active material is Si doped with M b metal, SiO w (Here, 0 < w ≤ 2), Si-C composite, etc. may also be acceptable. Although the capacity of the metal-doped silicon-based negative electrode active material decreases due to the doping element, it has high efficiency, so a high energy density can be realized.

[0093] In addition, the silicon-based negative electrode active material may, if necessary, further include a carbon coating layer on the surface of the particles. At this time, the carbon coating amount may be 20% by weight or less, preferably 0.1 - 20% by weight based on the total weight of the silicon-based negative electrode active material. When applying carbon coating, the electrical conductivity of the silicon surface is improved, the uniformity of the SEI layer is improved, and the initial efficiency and life characteristics are improved.

[0094] The carbon coating layer can be formed by methods such as dry coating, wet coating, chemical vapor deposition (CVD), physical vapor deposition (PVD), atomic layer deposition (ALD).

[0095] On the other hand, the silicon-based negative electrode active material preferably has a capacity of 1000 - 4000 mAh / g, preferably 1000 - 3800 mAh / g, more preferably 1200 - 3800 mAh / g. Using a silicon-based negative electrode active material that satisfies the above capacity range can realize high-capacity characteristics.

[0096] The silicon-based negative electrode active material may have an initial efficiency of 60 to 95%, 70 to 95%, and preferably 75 to 95%. The initial efficiency of the silicon-based negative electrode active material means a percentage of a discharge capacity relative to a charge capacity measured after a half cell is manufactured from a negative electrode using 100% of the silicon-based negative electrode active material as a negative electrode active material and a lithium counter electrode, and then the half cell is charged and discharged between 0.01 V and 1.5 V at a rate of 0.1 C. When the initial efficiency of the silicon-based negative electrode active material satisfies the above range, lithium provided from the positive electrode can be reversibly used, and excellent rapid charging performance can be realized.

[0097] In addition, the particle size D of the silicon-based negative electrode active material 50 is 3 μm to 8 μm, preferably 4 μm to 7 μm, and D min ~D max The particle size of the silicon-based negative electrode active material may be 0.01 μm to 30 μm, preferably 0.01 μm to 20 μm, and more preferably 0.5 μm to 15 μm. When the particle size of the silicon-based negative electrode active material satisfies the above range, sufficient electrode density can be ensured by mixing with a carbon-based negative electrode or by using it alone.

[0098] In addition, the negative electrode may further include a carbon-based negative electrode active material as a negative electrode active material, if necessary. The carbon-based negative electrode active material may be, but is not limited to, artificial graphite, natural graphite, graphitized carbon fiber, amorphous carbon, soft carbon, hard carbon, etc.

[0099] Meanwhile, the silicon-based negative electrode active material may be included in an amount of 1 to 100 wt %, 1 to 50 wt %, 1 to 30 wt %, 1 to 15 wt %, 10 to 70 wt %, or 10 to 50 wt % based on the total weight of the negative electrode active material.

[0100] The carbon-based negative electrode active material may be included in an amount of 0 to 99 wt%, 50 to 99 wt%, 70 to 99 wt%, 85 to 99 wt%, 30 to 90 wt%, or 50 to 90 wt%, based on the total weight of the negative electrode active material.

[0101] According to one embodiment, the negative electrode active material may be a mixture of a silicon-based negative electrode active material and a carbon-based negative electrode active material, and in this case, the mixing ratio of the silicon-based negative electrode active material and the carbon-based negative electrode active material may be 1:99 to 50:50, preferably 3:97 to 30:70, by weight ratio. When the mixing ratio of the silicon-based negative electrode active material and the carbon-based negative electrode active material satisfies the above range, the capacity characteristics are improved and the volume expansion of the silicon-based negative electrode active material is suppressed, thereby ensuring excellent cycle performance.

[0102] The negative electrode active material may be included in an amount of 80 wt % to 99 wt % based on the total weight of the negative electrode active material layer. When the content of the negative electrode active material is in the above range, excellent capacity characteristics and electrochemical characteristics can be obtained.

[0103] Examples of the conductive material include spherical or flaky graphite, carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, carbon fiber, single-walled carbon nanotube, multi-walled carbon nanotube, and other carbon-based materials, metal powder or metal fiber of copper, nickel, aluminum, silver, and other materials, conductive whiskers of zinc oxide, potassium titanate, and other materials, conductive metal oxides of titanium oxide, and conductive polymers of polyphenylene derivatives, and any one of these materials may be used alone or in combination of two or more. The conductive material may be contained in an amount of 0.1 to 30% by weight, 1 to 20% by weight, or 1 to 10% by weight based on the total weight of the negative electrode active material layer.

[0104] Preferably, the conductive material is a single-walled carbon nanotube. When the single-walled carbon nanotube is used as the conductive material, a conductive path is uniformly formed on the surface of the negative electrode active material, thereby improving cycle characteristics.

[0105] Examples of the binder include polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylic acid, polyacrylamide, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer rubber (EPDM rubber), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, and various copolymers thereof, and one of these can be used alone or a mixture of two or more can be used. The binder may be contained in an amount of 1 to 20% by weight, 2 to 20% by weight, or 2 to 10% by weight based on the total weight of the negative electrode active material layer.

[0106] The negative electrode may have a single-layered negative electrode active material layer or a multi-layered structure composed of two or more layers. When the negative electrode active material layer has a multi-layered structure composed of two or more layers, each layer may have a different type and / or content of the negative electrode active material, binder, and / or conductive material. For example, the negative electrode according to the present invention may be formed such that the lower layer has a higher content of the carbon-based negative electrode active material than the upper layer, and the upper layer has a higher content of the silicon-based negative electrode active material. In this case, compared to the case where the negative electrode active material layer is formed as a single layer, an effect of improving fast charging performance can be obtained.

[0107] On the other hand, the negative electrode active material layer may have a porosity of 20% to 70% or 20% to 50%. If the porosity of the negative electrode active material layer is too small, the electrolyte impregnation property may decrease, and lithium mobility may decrease, whereas if the porosity is too large, the energy density may decrease.

[0108] On the other hand, the lithium secondary battery of the present invention is preferably constructed with an N / P ratio, which is the ratio of the discharge capacity of the negative electrode to the discharge capacity of the positive electrode, being varied depending on the type of negative electrode active material used.

[0109] For example, when a mixture of SiO and a carbon-based negative electrode active material is used as the negative electrode active material, the N / P ratio may be about 100% to 150%, preferably 100% to 140%, and more preferably 100% to 120%. If the discharge capacity of the negative electrode relative to the discharge capacity of the positive electrode is out of the above range, the balance between the positive electrode and the negative electrode is not achieved, and there is a risk of deterioration of the life characteristics or the occurrence of lithium precipitation.

[0110] When 100% of Si is used as the negative electrode active material, the N / P ratio may be about 150% to 300%, preferably 160% to 300%, and more preferably 180% to 300%. If the discharge capacity of the negative electrode relative to the discharge capacity of the positive electrode is out of the above range, the balance between the positive electrode and the negative electrode is not achieved, and there is a risk of deterioration of the life characteristics or the occurrence of lithium precipitation.

[0111] The negative electrode may be manufactured by a method known in the art, for example, by coating a negative electrode slurry prepared by dissolving or dispersing a negative electrode active material and, optionally, a binder and a conductive material in a solvent on a negative electrode current collector, rolling and drying the slurry, or by casting the negative electrode slurry on a separate support, peeling off the support, and laminating the resulting film on the negative electrode current collector.

[0112] The negative electrode current collector is not particularly limited as long as it does not induce chemical changes in the battery and has high conductivity, and may be, for example, copper, stainless steel, aluminum, nickel, titanium, baked carbon, copper or stainless steel surface treated with carbon, nickel, titanium, silver, or aluminum-cadmium alloy. The negative electrode current collector usually has a thickness of 3 μm to 500 μm, and like the positive electrode current collector, the surface of the current collector may be formed with fine irregularities to strengthen the binding force of the negative electrode active material. For example, it may be used in various forms such as a film, sheet, foil, net, porous body, foam, or nonwoven fabric.

[0113] The solvent may be a solvent commonly used in the art, such as dimethyl sulfoxide (DMSO), isopropyl alcohol, N-methylpyrrolidone (NMP), acetone, or water, and one or more of these may be used alone or in combination. The amount of the solvent used is not particularly limited as long as it can be adjusted to an appropriate viscosity of the negative electrode slurry, taking into consideration the coating thickness of the negative electrode composite, production yield, workability, and the like.

[0114] Separator In the lithium secondary battery of the present invention, the separator separates the negative electrode and the positive electrode and provides a path for lithium ions to move. Any separator that is generally used in lithium secondary batteries can be used without any particular limitation, and in particular, a separator that has low resistance to the movement of electrolyte ions and has excellent electrolyte humidification ability is preferred. Specifically, a porous polymer film, for example, a porous polymer film made of a polyolefin polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, and an ethylene / methacrylate copolymer, or a laminate structure of two or more layers thereof can be used. In addition, a conventional porous nonwoven fabric, for example, a nonwoven fabric made of high-melting glass fiber, polyethylene terephthalate fiber, etc., may be used. In addition, in order to ensure heat resistance or mechanical strength, a coated separator containing a ceramic component or a polymeric substance may be used, and may be selectively used as a single layer or multilayer structure.

[0115] electrolyte Examples of the electrolyte used in the present invention include organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel-type polymer electrolytes, solid inorganic electrolytes, and molten inorganic electrolytes that can be used in the production of lithium secondary batteries, but are not limited to these.

[0116] Specifically, the electrolyte may include an organic solvent and a lithium salt.

[0117] The organic solvent can be used without any particular limitation as long as it can act as a medium through which ions involved in the electrochemical reaction of the battery can move. Specifically, the organic solvent can be an ester solvent such as methyl acetate, ethyl acetate, γ-butyrolactone, ε-caprolactone, etc.; an ether solvent such as dibutyl ether or tetrahydrofuran, etc.; a ketone solvent such as cyclohexanone, etc.; an aromatic hydrocarbon solvent such as benzene or fluorobenzene, etc.; dimethylcarbonate (DMC), diethylcarbonate (DEC), methylethylcarbonate (MEC), ethylmethylcarbonate (EMC), ethylene carbonate (EC), propylene carbonate (propylene carbonate), etc. Examples of solvents that can be used include carbonate solvents such as PC (carbonate), alcohol solvents such as ethyl alcohol and isopropyl alcohol, nitriles such as R-CN (R is a straight-chain, branched, or cyclic hydrocarbon group having 2 to 20 carbon atoms, which may contain a double bond, aromatic ring, or ether bond), amides such as dimethylformamide, dioxolanes such as 1,3-dioxolane, and sulfolanes.

[0118] The lithium salt can be any compound that can provide lithium ions used in lithium secondary batteries without any particular limitations. Specifically, the anion of the lithium salt is F - , Cl - , Br - , I - , NO3 - , N(CN)2 - , BF4 - , CF3CF2SO3- , (CF3SO2)2N - , (FSO2)2N - , CF3CF2(CF3)2CO - , (CF3SO2)2CH - , (SF5)3C - , (CF3SO2)3C - , CF3(CF2)7SO3 - , CF3CO2 - , CH3CO2 - , SCN - , and (CF3CF2SO2)2N - Examples of the lithium salt include at least one selected from the group consisting of LiPF6, LiN(FSO2)2, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiN(C2F5SO2)2, LiN(CF3SO2)2.LiCl, LiI, LiB(C2O4)2, etc. The concentration of the lithium salt is preferably within the range of 0.1 to 5.0M.

[0119] The electrolyte may contain additives for the purpose of improving the life characteristics of the battery, suppressing the capacity decrease, suppressing gas generation, etc. Examples of the additives include various additives used in the art, such as fluoroethylene carbonate (FEC), vinylene carbonate (VC), vinyl ethylene carbonate (VEC), ethylene sulfate (ESa), lithium difluorophosphate (LiPO2F2), lithium bisoxalate borate (LiBOB), lithium tetrafluoroborate (LiBF4), lithium difluorooxalate borate (LiDFOB), lithium difluorobisoxalate phosphate (LiDFBP), lithium tetrafluorooxalate phosphate (LiTFOP), lithium methyl sulfate (LiMS), lithium ethyl sulfate (LiES), propane sultone (PS), propene sultone (PRS), succinonitrile (SN), adiponitrile (AND), 1,3,6-hexanetricarbonitrile (HTCN), 1,4-dicyano-2-butene (DCB), fluorobenzene (FB), ethyl di(prop-2-yn-1-yl)phosphate (EDP), 5-methyl-5-propargyloxylcarbonyl-1,3-dioxane-2-one (MPOD), a compound represented by the following chemical formula A (chemical formula 1) (e.g., cyanoethyl polyvinyl alcohol, PVA-CN), a compound represented by the following chemical formula B (chemical formula 2) (e.g., heptafluorobutyl cyanoethyl polyvinyl alcohol, PF-PVA-CN), a compound represented by the following chemical formula C (chemical formula 3) (e.g., propargyl 1H-imidazole-1-carboxylate, PAC), and / or a compound represented by the following chemical formula D (chemical formula 4) (e.g., aryl imidazole such as C6H8N2), etc. may be used.

[0120] [ka]

[0121] In the above chemical formula A (Chemical Formula 1), m and n each independently represent an integer of 1-100.

[0122] [ka]

[0123] [ka]

[0124] In the above chemical formula C (Chemical Formula 3), R 16 is a linear or non-linear alkylene group having 1 to 3 carbon atoms; R 17 ~R 19 are each independently at least one selected from the group consisting of hydrogen, an alkyl group having 1 to 3 carbon atoms, and -CN, and D is CH or N.

[0125] [ka]

[0126] In the above chemical formula D (Chemical Formula 4), R1, R2, R3, and R4 each independently represent a hydrogen atom; or an alkyl group having 1 to 5 carbon atoms, a cyano group (CN), an allyl group, a propargyl group, an amine group, a phosphate group, an ether group, a benzene group, a cyclohexyl group, a silyl group, an isocyanate group (-NCO), or a fluoro group (-F).

[0127] Preferably, the additive may be a compound that acts as an oxygen scavenger. In addition to tristri(methylsilyl)phosphite (TMSPi), tristrimethylphosphite (TMPi), and tris(2,2,2-trifluoroethyl)phosphite (TTFP), substances with structures based on phosphite (see Chemical Formula E (Chemical Formula 5)), tristri(methylsilyl)phosphate (TMSPa), polyphosphate trimethylsilyl ester (PPSE), tris(pentafluorophenyl)borane (TPFPB), coumarin-3-carbonitrile (CMCN), 7-ethynylcoumarin (ECM), 3 -Acetyl coumarin (AcCM), 3-[(trimethylsilyl)oxyl]-2H-1-benzopyran-2-one (TMSOCM), 3-(trimethylsilyl)coumarin (TMSCM), 3-(2-propyn-1-yloxyl)-2H-1-benzopyran-2-one (POCM), 2-propyn-1-yl-2-oxo-2H-1-benzopyran-3-carboxylate (OBCM), and other compounds having a coumarin structure (see chemical formula F (chemical formula 6)) can be used as compounds that act as oxygen scavengers.

[0128] [ka]

[0129] [ka]

[0130] In the above chemical formula E (Chemical Formula 5) and chemical formula F (Chemical Formula 6), R1 to R6 are each independently a substituted or unsubstituted alkenyl group having 2 to 20 carbon atoms, and a substituted or unsubstituted alkynyl group having 2 to 20 carbon atoms, which may contain cyan (nitrile), fluoro (F), ether (COC), carboxyl (OC=O), trimethylsilyl (-TMS), isocyanate (-NCO), and / or isothiocyanate (-NCS) functional groups.

[0131] The lithium secondary battery according to the present invention can be effectively used in portable devices such as mobile phones, notebook computers, and digital cameras, and in electric vehicles such as hybrid electric vehicles (HEVs).

[0132] According to another embodiment of the present invention, there is provided a battery module including the lithium secondary battery as a unit cell, and a battery pack including the same.

[0133] The battery module or battery pack can be used as a power source for one or more medium- to large-sized devices, including power tools; electric vehicles, including electric vehicles (EVs), hybrid electric vehicles, and plug-in hybrid electric vehicles (PHEVs); and power storage systems.

[0134] The external shape of the lithium secondary battery of the present invention is not particularly limited, and may be a cylindrical shape using a can, a square shape, a pouch shape, a coin shape, or the like.

[0135] The lithium secondary battery according to the present invention can be used not only as a battery cell used as a power source for small devices, but also suitably as a unit battery in a medium- to large-sized battery module containing a large number of battery cells.

[0136] The present invention will now be described in more detail with reference to specific examples.

[0137] Example 1 Average particle size D 50 3μm Ni 0.25 Mn 0.75(OH)2 and lithium hydroxide (LiOH) were added to a Henschel mixer (700 L) so that the molar ratio of Li:transition metals (Ni+Mn) was 1.4:1, and mixed at 300 rpm for 20 minutes. The mixed powder was placed in an alumina crucible measuring 330 mm x 330 mm, and maintained at 500°C for 10 hours in an oxygen atmosphere, and then calcined at 900°C for 30 hours to produce a positive electrode active material powder. An SEM image of the produced positive electrode active material powder is shown in Figure 1. It can be seen from Figure 1 that the produced positive electrode active material powder has a morphology in which single particles and pseudo-single particles are mixed.

[0138] Example 2 Average particle size D 50 3μm Ni 0.35 Mn 0.65 (OH)2 and lithium hydroxide (LiOH) were added to a Henschel mixer (700L) so that the molar ratio of Li:transition metals (Ni+Mn) was 1.33:1, and mixed at 300 rpm for 20 minutes. The mixed powder was placed in an alumina crucible of 330mm x 330mm size, and maintained at 500℃ for 10 hours in an oxygen atmosphere, and then calcined at 900℃ for 30 hours to produce perlithiated manganese oxide.

[0139] The perlithiated manganese oxide and aluminum oxide were mixed and then heat-treated to produce a positive electrode active material powder in which the surface of the perlithiated manganese oxide was coated with 1500 ppm of Al.

[0140] Example 3 Average particle size D 50 5μm Ni 0.35 Mn 0.65 (OH)2 and lithium hydroxide (LiOH) were added to a Henschel mixer (700L) so that the molar ratio of Li:transition metals (Ni+Mn) was 1.33:1, and mixed at 300 rpm for 20 minutes. The mixed powder was placed in an alumina crucible of 330mm x 330mm size, and maintained at 500℃ for 10 hours in an oxygen atmosphere, and then calcined at 950℃ for 30 hours to produce perlithiated manganese oxide.

[0141] The perlithiated manganese oxide and aluminum oxide were mixed and then heat-treated to produce a positive electrode active material powder in which the surface of the perlithiated manganese oxide was coated with 1500 ppm of Al.

[0142] Example 4 Average particle size D 50 0.8μm Ni 0.25 Mn 0.75 (OH)2 and lithium hydroxide (LiOH) were added to a Henschel mixer (700 L) so that the molar ratio of Li:transition metals (Ni+Mn) was 1.4:1, and mixed at 300 rpm for 20 minutes. The mixed powder was placed in an alumina crucible of 330 mm x 330 mm size, and maintained at 500°C for 10 hours in an oxygen atmosphere, and then calcined at 850°C for 30 hours to produce a positive electrode active material powder.

[0143] Example 5 Average particle size D 50 1.0μm Ni 0.35 Mn 0.65 (OH)2 and lithium hydroxide (LiOH) were added to a Henschel mixer (700L) so that the molar ratio of Li:transition metals (Ni+Mn) was 1.33:1, and mixed at 300 rpm for 20 minutes. The mixed powder was placed in an alumina crucible of 330mm x 330mm size, and maintained at 500℃ for 10 hours in an oxygen atmosphere, and then calcined at 850℃ for 30 hours to produce perlithiated manganese oxide.

[0144] The perlithiated manganese oxide and aluminum oxide were mixed and then heat-treated to produce a positive electrode active material powder in which the surface of the perlithiated manganese oxide was coated with 1500 ppm of Al.

[0145] Example 6 Average particle size D 50 1.8μm Ni 0.25 Mn 0.75(OH)2 and lithium hydroxide (LiOH) were added to a Henschel mixer (700 L) so that the molar ratio of Li:transition metals (Ni+Mn) was 1.4:1, and mixed at 300 rpm for 20 minutes. The mixed powder was placed in an alumina crucible of 330 mm x 330 mm size, and maintained at 500°C for 10 hours in an oxygen atmosphere, and then calcined at 880°C for 30 hours to produce a positive electrode active material powder.

[0146] Comparative Example 1 A positive electrode active material powder was prepared in the same manner as in Example 1, except that after maintaining at 500°C for 10 hours, the material was calcined at 850°C for 10 hours instead of at 900°C for 30 hours. A SEM image of the prepared positive electrode active material powder is shown in Figure 2. From Figure 2, it can be seen that the particles of the prepared positive electrode active material are in the form of secondary particles formed by agglomeration of several hundred primary particles.

[0147] Experimental Example 1 The average particle size D of the positive electrode active material powders produced in Examples 1 to 6 and Comparative Example 1 50 The average particle size of the nodules / primary particles was measured. 50 was measured using a Microtrac MT 3000 and the average particle size of the nodules / primary particles was measured by SEM image analysis.

[0148] The measurement results are shown in Table 1 below.

[0149] [Table 1]

[0150] <Manufacturing lithium secondary batteries> Each of the positive electrode active materials prepared in Examples 1 to 6 and Comparative Example 1, carbon nanotubes, and a PVDF binder were mixed in a weight ratio of 92.5:3.0:4.5 in N-methylpyrrolidone to prepare a positive electrode slurry.

[0151] The positive electrode slurry was applied onto an aluminum current collector sheet, dried, and then rolled to prepare a positive electrode.

[0152] A negative electrode active material (SiO:graphite=5:95 weight ratio), carbon nanotubes, styrene-butadiene rubber (SBR), and carboxymethyl cellulose (CMC) were mixed in water in a weight ratio of 96.2:0.8:2:1 to prepare a negative electrode slurry.

[0153] The negative electrode slurry was applied onto a copper current collector sheet, dried, and then rolled to prepare a negative electrode.

[0154] An electrode assembly was prepared by interposing a separator between the positive electrode and the negative electrode prepared as described above. The electrode assembly was inserted into a battery case, and an electrolyte was injected to assemble a lithium secondary battery. The battery was then charged at a constant current of 0.1 C at 45° C. up to 4.65 V, and then discharged at a constant current of 0.1 C down to 2.0 V to perform an activation process.

[0155] Experimental Example 2 The lithium secondary battery manufactured as described above was stored at 60° C. for 4 weeks, and then the amount of gas generated (unit: μL / Ah) was measured. The measurement results are shown in Table 2 below.

[0156] Experimental Example 3 The secondary battery was charged at 25° C. at a constant current of 0.33 C until it reached 4.4 V, and then discharged at a constant current of 0.33 C until it reached 2.5 V, forming one cycle. The number of cycles at which the discharge capacity after the cycle reached 80% of the initial discharge capacity was measured while repeating the charge and discharge. The measurement results are shown in Table 2 below.

[0157] [Table 2]

[0158] From Table 2 above, it can be seen that the lithium secondary batteries of Examples 1 to 6, in which perlithiated manganese oxide in the form of single particle / pseudo-single particle is used, generate less gas and have superior life characteristics compared to the lithium secondary battery of Comparative Example 1, in which perlithiated manganese oxide in the form of secondary particles is used.

Claims

1. The perlithiated manganese-based oxide particles are represented by the following chemical formula 1: The perlithiated manganese oxide particles are in the form of a single particle consisting of one nodule or a quasi-single particle which is a composite of 2 to 30 nodules; [Chemical formula 1] Li a Ni b Co c Mn d M e O 2 In the above Chemical Formula 1, 1<a, 0≦b≦0.5, 0≦c≦0.1, 0.5≦d<1.0, 0≦e≦0.2, and M is at least one selected from the group consisting of Al, B, Co, W, Mg, V, Ti, Zn, Ga, In, Ru, Nb, Sn, Sr, and Zr.

2. 2. The positive electrode active material powder according to claim 1, wherein the positive electrode active material powder is made of perlithiated manganese oxide particles having at least one of the form of a single particle and a quasi-single particle.

3. The average particle size D of the positive electrode active material powder 50 The positive electrode active material powder according to claim 1 , wherein the particle size is 7.0 μm or less.

4. 2. The positive electrode active material powder according to claim 1, wherein, in Chemical Formula 1, 1.1≦a≦1.5, 0.1≦b≦0.4, 0≦c≦0.05, 0.5≦d≦0.80, and 0≦e≦0.

1.

5. 2. The positive electrode active material powder according to claim 1, wherein the perlithiated manganese oxide particles have a crystal structure in which a layered structure phase and a rock salt structure phase are mixed.

6. 2. The positive electrode active material powder according to claim 1, wherein the nodules have an average particle size of 0.5 μm to 3.5 μm.

7. 2. The positive electrode active material powder according to claim 1, wherein the perlithiated manganese oxide particles have a crystallite size of 30 nm to 400 nm.

8. A positive electrode comprising the positive electrode active material powder according to claim 1 .

9. The positive electrode according to claim 8 , a negative electrode including a negative electrode active material; a separator interposed between the positive electrode and the negative electrode; and an electrolyte.

10. The lithium secondary battery according to claim 9 , wherein the negative electrode comprises a silicon-based negative electrode active material.

11. 10. The lithium secondary battery of claim 9, wherein the negative electrode comprises a mixture of a silicon-based negative electrode active material and a carbon-based negative electrode active material.

12. The negative electrode active material is made of silicon (Si), 10. The lithium secondary battery according to claim 9, wherein the N / P ratio of the lithium secondary battery is 150% to 300%.

13. the negative electrode active material is a mixture of silicon oxide and a carbon-based negative electrode active material, 10. The lithium secondary battery according to claim 9, wherein the N / P ratio of the lithium secondary battery is 100% to 150%.

Citation Information

Patent Citations

  • Lithium-rich manganese-based positive electrode material and preparation method thereof, and lithium ion battery

    CN104966831A

  • Solid-phase reaction synthesis method of electrode active material single crystal

    CN111485278A

  • Lithium ion battery positive pole piece and preparation method thereof

    CN113793913A

  • Polycrystalline lithium manganese oxide particles, method for producing the same, and positive electrode active material containing the same

    JP2016509567A

  • Cathode active material

    JP2019091719A